Strategi Pemberdayaan Usaha Mikro,Kecil,dan Menengah (UMKM) di dinas koperasi dan UKM Kabupaten Tabanan - Ida Ayu Anika Mahayani; I Putu Dharmanu Yudartha; Ni Putu Anik Prabawati (CV. Lenggogeni Data Publishing, 2024)
This research aims to understand the empowerment strategy for Micro, Small and Medium Enterprises (MSMEs) in the cooperative and SME department of Tabanan Regency. This research uses a qualitative descriptive method with data analysis using SWOT matrix analysis. Data collection techniques are carried out through interviews, observation and documentation. The technique for determining informants used was the snowball and purposive techniques. The results of this research show that there are still indicators that are not optimal. The SWOT analysis shows that the Tabanan Regency cooperative and SME department has large and abundant potential but also faces challenges such as market expansion, changes in regulations and increasingly fierce competition. The empowerment strategy involves improving facilities, services and promotions as well as training through digital media. Sustainability is integrated into management to involve local communities and improve human resources. The implementation of this strategy is expected to increase people's interest in loving local products and using local products so that local products can compete with foreign products, as well as creating economic opportunities for local communities. Collaboration with related parties is needed to support this empowerment. With a holistic approach, the Tabanan Regency Cooperatives and SMEs Service is expected to be an agent of change capable of integrating economic, social and environmental aspects in efforts to empower MSMEs. Abstrak Penelitian ini bertujuan memahami strategi pemberdayaan Usaha Mikro,kecil dan menengah (UMKM) di dinas koperasi dan UKM Kabupaten Tabanan. Penelitian ini menggunakan meggunakan metode deskriptif Kualitatif dengan analisis data menggunakan analisis matriks SWOT. Teknik pengumpulan data dilakukan melalui wawancara,observasi,dan dokumentasi. Teknik penentuan informan yang digunakan adalah Teknik snowball dan purposive. Hasil penelitian ini menunjukan masih adanya indikator yang belum maksimal. Analisis SWOT menunjukkan bahwa dinas koperasi dan UKM Kabupaten Tabanan memiliki poteni yang besar serta melimpah namun juga menghadapi tantangan seperti peluasan pasar, perubahan regulasi dan persaingan yang semakin ketat. Strategi pemberdayaan melibatkan peningkatan fasilitas,pelayanan dan promosi serta pelatihan melalui media digital. Keberlanjutan diintegrasikan dalam manajemen untuk melibatkan komunitas lokal dan peningkatan SDM. Implementasi strategi ini diharapkan dapat meningkatkan minat masyarakat untuk mencintai produk lokal dan menggunakan produk lokal sehingga produk lokal dapat bersaing dengan produk luar, serta menciptakan peluang ekonomi bagi masyarakat setempat. Kolaborasi dengan pihak terkait diperlukan untuk mendukung pemberdayaan ini. Dengan pendekatan holistic, Dinas Koperasi dan UKM Kabupaten Tabanan diharapkan dapat menjadi agen perubahan yang mampu mengintegrasikan aspek – aspek ekonomi,sosial,dan lingkungan dalam upaya pemberdayaan UMKM. Kata Kunci: Usah mikro,Kecil dan Menengah,Strategi Pemberdayaan,Potensi Daerah, SWOT